Influence of Different Lubricating Media on Ultrasonic Retrieval Efficiency of Fractured Instruments from Curved Root Canals: An ex vivo study - Saxena, Tanushree; Ranjan, Manish (Journal of Neonatal Surgery, 2025)
Introduction: Ultrasonic retrieval of fractured instruments is a technique-sensitive procedure and may be influenced by the properties of the fluid medium (such as viscosity, lubricity, and surface tension) used during activation. Conventional chelators such as ethylenediaminetetraacetic acid (EDTA) and novel plant-derived alternatives such as soybean oil have been suggested to facilitate retrieval by enhancing lubrication, cavitation, and acoustic streaming. This study aimed to compare the effect of 17% EDTA, soybean oil, and saline on the success rate and efficiency of ultrasonic retrieval of fractured instruments in curved canals. Materials and Methods: Thirty extracted mandibular molars with mesiobuccal canal curvature of 20°–30° (Schneider’s method) were selected. A 4-mm ProTaper Gold F2 fragment was intentionally fractured and confirmed radiographically. Ultrasonic troughing was performed under a dental operating microscope. Teeth were randomly assigned into three groups (n = 10): Group 1 – 17% EDTA, Group 2 – soybean oil, Group 3 - 0.9% saline. Following initial mobility, 2 mL of the assigned fluid was introduced followed by ultrasonic activation along inner curvature. Retrieval time was recorded from first visible mobility until retrieval, with a 30-minute cutoff. Results: Success rates were 100% for EDTA, 90% for soybean oil, and 80% for saline, with no significant difference (p > 0.05). Mean retrieval times were 15.2 ± 1.8 min for EDTA, 14.3 ± 1.7 min for soybean oil, and 24.1 ± 2.3 min for saline with one-way ANOVA showing significant differences (p < 0.001). Post hoc analysis confirmed both EDTA (p < 0.01) and soybean oil (p < 0.001) enabled faster retrieval than saline, while no difference was observed between EDTA and soybean oil. Conclusion: Both EDTA and soybean oil significantly enhanced the efficiency of ultrasonic retrieval compared with saline, reducing retrieval time without compromising success rates. Further in vivo studies are required to validate safety, biocompatibility, and long-term effects.